Otimização e validação de métodos de extração e quantificação do inseticida dinotefuran em amostras de água e solo - Sandro Braga Soares (2023)
The dinotefuran is a compound belonging to the third generation of nicotinoid insecticides, has been effective in combating pests resistant to conventional insecticides, such as organophosphates, carbamates and pyrethroids. This molecule has high solubility in water (39.830 g L-1 at 25 oC) which facilitates its dragging and leaching to the lower layers of the soil. The present study aimed to improve and validate liquid-liquid extraction with low temperature purification (LLE-LTP) and solid liquid extraction with low temperature purification (SLE-LTP) to determine dinotefuran residues in water and soil samples, respectively, by high performance liquid chromatography with diode array detector (HPLC-DAD). The results revealed that the analyses recovery ranged from 85.44 to 92.88 % with a relative standard deviation less than 8.50 % for both matrices. LLE-LTP and ESL-LTP were selective, precise, accurate, linear in the ranges of 10.0 to 210 µg L-1, and 15.0 to 140 µg Kg-1 for water and soil, respectively. The detection and quantification limits were 5.00 and 10.00 µg L-1 for water and 10 and 15 µg kg-1 for soil. The matrix effect was less than 14 and 15% for water and soil respectively. The study of dinotefuran stability in water revealed significant persistence in the absence of light (>130 days), and a half-life of seven days in water exposed to sunlight. It was not possible to detect dinotefuran in real water and soil samples collected in the southern region of the state of Minas Gerais. LLE-LTP and ESL-LTP coupled with HPLC-DAD analysis presented itself as a simple, easy to perform and efficient method for extracting and analyzing dinotefuran both water and soil samples.